2021
DOI: 10.1186/s10194-021-01302-x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of microglial GLP-1R in the trigeminal nucleus caudalis suppresses central sensitization of chronic migraine after recurrent nitroglycerin stimulation

Abstract: Background Central sensitization is considered a critical pathogenic mechanism of chronic migraine (CM). Activation of microglia in the trigeminal nucleus caudalis (TNC) contributes to this progression. Microglial glucagon-like peptide-1 receptor (GLP-1R) activation can alleviate pain; however, whether it is involved in the mechanism of CM has not been determined. Thus, this study aims to investigate the precise role of GLP-1R in the central sensitization of CM. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 64 publications
2
14
0
Order By: Relevance
“…Recent evidence suggests that TEN enhances the positive effects of GLP-1 [18]. Several previous studies have concluded that activation of GLP-1R can effectively suppress neuroinflammation and central sensitization, thereby alleviating neuropathic pain in various animal models [19][20][21][22][23][24][25]. Furthermore, in the CNS, GLP-1R is confined to microglial cells of the spinal dorsal horn and greatly decreased after nerve injury and has been found to play a key role in microglial cell activation [19,26].…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence suggests that TEN enhances the positive effects of GLP-1 [18]. Several previous studies have concluded that activation of GLP-1R can effectively suppress neuroinflammation and central sensitization, thereby alleviating neuropathic pain in various animal models [19][20][21][22][23][24][25]. Furthermore, in the CNS, GLP-1R is confined to microglial cells of the spinal dorsal horn and greatly decreased after nerve injury and has been found to play a key role in microglial cell activation [19,26].…”
Section: Introductionmentioning
confidence: 99%
“…The results suggested that the astrocytes in the TNC were activated from 20 d to at least 47 d. We also detected Iba1 in the TNC, a biomarker of microglial activation, at transcription level through RNAscope ISH, and the results suggested that the microglia were activated at the same time with astrocytes. Microglia may contribute to the central sensitization through modulating cytokine signals communication among the astrocytes, microglia, and neurons [12,[24][25][26][27]. The duration of astrocytic and microglial activation is consistent with the sensitization of the trigeminovascular system.…”
Section: Discussionmentioning
confidence: 66%
“…GFAP is thought to be an important biomarker of astrocytic activation. Altered levels of proinflammation cytokines in plasma and serum, such as interleukin 1 beta (IL-1β), interleukin 6 (IL-6), and tumor necrosis factor alpha (TNF-α), has been demonstrated the correlation to migraine in both patients and animals [9][10][11][12]. But it remains unclear whether the levels change of cytokines in the TNC tissue and serum are correlated to the central sensitization and astrocytic activation in the TNC region in CM.…”
Section: Introductionmentioning
confidence: 99%
“…Amounts of evidences supported the significance role of the PI3K-Akt signaling pathway in migraine [ 45 , 56 ]. A study has confirmed that glucagon-like peptide-1 receptor (GLP-1R) agonist inhibited the upregulation of PI3K/p-Akt in the trigeminal nucleus caudalis (TNC) via Western blotting, which indicated that microglial GLP-1R activation in TNC may suppress the central sensitization of chronic migraine by regulating TNC microglial activation via the PI3K/Akt pathway [ 57 ]. Furthermore, PRKCA, as a core target of our research in both the P13K-AKT pathway and MAPK signaling pathway, is calcium-activated and phospholipid and diacylglycerol (DAG)-dependent serine/threonine-protein kinase activating signaling cascade involving MAPK1/3 (ERK1/2) and RAP1GAP, thus promoting cell growth by phosphorylating and activating RAF1.…”
Section: Resultsmentioning
confidence: 99%